OP0127 Impact of Disease Activity and Treatment on Progression of Functional Limitation in RA. (10th June 2014) - Norton, S.; Nikiphorou, E.; Carpenter, L.; Walsh, D.; Dixey, J.; Kiely, P.; Young, A.
Abstract : Background: Functional limitation is a key outcome in rheumatoid arthritis and a key driver of the cost of RA in health economic models. Due to restrictive inclusion/exclusion criteria and short follow up, RCTs estimate treatment effects that may not reflect the actual impact of treatment on HAQ progression in the RA population. Objectives: To estimate the rate of progression in functional limitation in a two large RA inception cohorts under different disease activity and treatment scenario's. Methods: The analysis combined data from two large UK inception cohorts: Early Rheumatoid Arthritis Study (ERAS, N=1460) and Early Rheumatoid Arthritis Network (ERAN, N=1236). Recruitment to ERAS was between 1986 and 1998, and ERAN 2003 and 2012. Functional limitation was assessed using the Health Assessment Questionnaire (HAQ) and disease activity using the Disease Activity Score (DAS28). Patients were grouped by DAS28 into low (≤3.2), moderate-low (>3.2 and ≤4.2), moderate-high (>4.2 and ≤5.1), and high (>5.2) disease activity groups based on their mean DAS28 over the course of follow up. The rate of HAQ progression was estimated using linear mixed effects regression models, including a random intercept and a random slope for time. The random effects allow the baseline level of HAQ and rate of change in HAQ to vary across individuals. Time dependant covariates were included in the model to account for disease modifying treatment: DMARD monotherapy, DMARD combination therapy, and biologic therapy. Interaction terms were included for all treatment related variables with time and DAS group, to allow for differential rates of progression by treatment over time. The analysis controlled for use of steroids, and orthopaedic surgery. Results: The total number of observations where both HAQ and DAS28 were recorded was 12, 536 (2, 372 patients, mean 5.2 observations per person), with visits ranging between the period 1988 and 2012 (median year 2000, inter-quartile range 1996 to 2004). The most common treatment profile was DMARD monotherapy (58%), under this treatment HAQ progression was 0.043 units per year (95% CI 0.037 to 0.049). For combination DMARD treatment (15%) HAQ progression was 0.033 (95% CI 0.019 to 0.046). Biologic therapy was used only rarely (3%) with an estimated rate of HAQ progression of 0.019 (95% CI -0.004 to 0.042). For patients on DMARD therapy the rate of HAQ progression followed a dose-response pattern by disease activity group: low disease activity = 0.014 (95% CI 0.005 to 0.024); moderate-low = 0.039 (95% CI 0.029 to 0.049); moderate-high = 0.064 (95% CI 0.053 to 0.074); and high = 0.080 (95% CI 0.066 to 0.093). Conclusions: Different rates of HAQ progression were observed for different treatment profiles. Patients with higher average levels of disease activity over the course of disease experienced faster rates of progression. Individuals with persistently low disease activity treated with DMARDS experienced rates of HAQ progression similar to those observed as a result of ageing in the general population [1]. References: Sokka T, Kautiainen H, Hannonen P, Pincus T. Arthritis Rheum. 2006;54(10):3113-8 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3148